2016
DOI: 10.1080/17470919.2016.1164244
|View full text |Cite
|
Sign up to set email alerts
|

Maternal buffering of fear-potentiated startle in children and adolescents with trauma exposure

Abstract: Parental availability influences fear expression and learning across species, but the effect of maternal buffering on fear learning in humans is unknown. Here we investigated the effect of maternal availability during fear conditioning in a group of children (ages 8–10) and adolescents (ages 11–13) from a low-income population with a range of trauma exposure. Acoustic startle response data were collected to measure fear-potentiated startle (FPS) in 104 participants. A total of 62 participants were tested with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 54 publications
(74 reference statements)
0
41
1
Order By: Relevance
“…Aspects of the rearing environment can buffer against the negative effects of early-life stress, including trauma [64]. In addition, social buffering provides a powerful protective influence against stress and changes with development such that maternal presence provides greatest buffering influence through middle childhood and less so during adolescence [80]. Importantly, the potential to benefit from social support in adulthood is thought to depend on maternal availability during childhood [82].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Aspects of the rearing environment can buffer against the negative effects of early-life stress, including trauma [64]. In addition, social buffering provides a powerful protective influence against stress and changes with development such that maternal presence provides greatest buffering influence through middle childhood and less so during adolescence [80]. Importantly, the potential to benefit from social support in adulthood is thought to depend on maternal availability during childhood [82].…”
Section: Discussionmentioning
confidence: 99%
“…In an fMRI study, children showed dampened amygdala activation to pictures of their mother compared to pictures of a stranger, whereas there was no difference in adolescents [79]. In another study that used fear conditioning of startle responses, children showed an attenuated fear response to a safety signal when the mother was available during conditioning [80]. However, when the mother was not in the same room, children were not able to discriminate danger and safety signals.…”
Section: Early Environmental Factors Influencing Risk For Ptsdmentioning
confidence: 99%
See 2 more Smart Citations
“…Cues that signal maternal presence are associated with dampened amygdala reactivity and greater mPFC-amygdala functional connectivity in children, particularly those who have a supportive relationship with their mother [40]. Similarly, maternal presence enhances threat-safety discrimination during fear conditioning in children [41]. Critically, amygdala reactivity to threatening cues following trauma exposure is weaker in children with high maternal support [42].…”
Section: Protective Factorsmentioning
confidence: 99%